Factors that motivate share buybacks : evidence from the Malaysian Listed Companies / Akma Hidayu Dol@Abdul Wahid - Dol, Akma Hidayu (2006)
This study identifies the underlying constructs of the motivating factors of share buyback decisions of Malaysian companies to share buybacks from 1999 to 2005. This study employs factor analysis to seek variables (indicators) on the factors and conform to what are the underlying motivations for companies to buyback shares. The indicator variables are selected on the basis of prior literature and factor analysis is used to see if these variables are the underlying constructs that motivate companies to exercise share buyback. This study reveals indicator variables like return on equity (ROE), earning per shares (EPS), return on assets (ROA) and market to book value of equity (MB) are the underlying constructs for improvement in the operating performance of the buyback companies. This study also reveals that intangible assets (INTANG), capital expenditures (CAPEXP) and sales (SALES) are the underlying constructs for undervaluation of companies' share prices. The results suggest that share buybacks merely a result of decrease in the denominator i.e. numbers of outstanding shares and intangible assets are source of undervaluation of the companies' share prices which is consistent to results of the prior studies. This suggests that companies' potential earnings are merely generated from intangibles. As a result, investors must interpret the earnings with caution focusing on the potential earnings of a buyback company.